Inclusive Tourism in Public Spaces: An Accessibility and Visitor Experience Study of Mobility-Impaired Individuals on Malioboro Street - Zachary Ryan; Mohamad Rachmadian Narotama; Iswan Bahri; Hikmah Kamarudin (ASEAN Journal on Hospitality and Tourism, 2026)
Everyone has the right to tourism, including individuals with disabilities. Unfortunately, not all tourist destinations can ensure a positive experience for disabled travelers. For instance, even popular sites like Malioboro Street in Yogyakarta may fail to provide an accessible and inclusive experience for people with disabilities. This study investigates the experiences of wheelchair users regarding facilities, culinary areas, and community responses in the Malioboro Street area. The research methodology employed in-depth interviews, observational fieldwork, and data documentation. Interviews were conducted with 10 participants who were wheelchair users and had visited Malioboro Street. The findings reveal that wheelchair-using tourists could not provide positive feedback on the facilities, culinary zones, or community responses in the area. This is attributed to the lack of accessibility in navigating facilities and dining areas, which were not adequately designed for wheelchair users. Additionally, the low awareness among local residents and workers–such as street vendors and shop staff–in assisting disabled tourists with special needs further contributed to their negative experiences. These barriers hindered participants from forming favorable impressions, underscoring the need for improved accessibility and inclusive practices in public tourism spaces.